Comments on information erasure in black hole - Alvi, Mishkat Al; Matin, Md. Abdul; Rahat, Moinul Hossain; Roy, Avik; Majumdar, Mahbub (© 2014 World Scientific Publishing Co. Pte Ltd, 2016)
This article was published in Modern Physics Letters A [© 2014 World Scientific Publishing Company.] and the definite version is available at: http://dx.doi.org/10.1142/S0217732314501995. The Article's website is at:http://www.worldscientific.com/doi/10.1142/S0217732314501995